GRANULOMETRIC MODELS OF ZARIA BANTAMENSIS BEDS AT BOJONG AND BAYAH AREA, IN BANTEN PROVINCE - Hita Pandita (KURVATEK, 2019)
Several research on mollusk fossils have been done in Indonesia. So far research was focused in the identification of species. Although thestudy ofrelationshipsbetween mollusks fossilsand their environment is important, only a few studies have been carried out it in Indonesia. The present study is aimed to reveal the relationships of genus Zaria appearance and sedimentation mechanism and expected to provide an overview of environmental model of Zaria. The methods used are field surveys, laboratory analysis and identification of morphological character of Zaria. Field surveys were conducted in two sites of discovery of Zaria bantamensis fossil in Bayah and Bojong areas. Laboratory work composes of granulometricand statistical analysis of biometric Zaria.The results showed that Zaria bantamensis appeareancewas associated with the rocks of poor sorting characteristics, with medium to fine sand grain sizes. Based on Visher curve the sedimentation mechanism of Bojong samples was dominated by saltation and in Bayah samples was thesuspensions. The results also indicate a possible relationship between shell length and sedimentation mechanism conditions.